THE NPFM IN EMERGING ECONOMIES: THE MODIFIED BUDGETING SYSTEM (MBS) IN MALAYSIAN GOVERNMENT - Muslim Har Sani Mohamad; Yusuf Karbhari (Universitas Trisakti, 2010)
This study examines the impact of the MBS on overall financial management in the Malaysian central government organisations. This study adopted cross sectional survey with two main stages of data collection - questionnaire and interview surveys. Providing evidence on the applicability of NPFM in developing countries, generally the respondents agreed that the MBS had improved financial management processes of their organisations by virtue of Expenditure Target, greater autonomy to operational managers and result based performance measures. However, structural weaknesses related to annuality and resistance to change by managers might undermine the reforms. Problems including shortfall of allocations and delays in receiving funds at responsibility centres should be addressed by the government. More importantly, this study provides evidence about the effectiveness of the NPFM mechanisms, which has its western origin, to civil service organisations in emerging economies.Keywords : New Public Financial Management (NPFM), Modified Budgeting System (MBS), Evaluation, Emerging Economies, Malaysia, Financial Management